UNILATERAL ECTOPIC TESTES IN A DOG - KANTHARAJ, S; SUDHA, G; JAYAKUMAR, C; LAKSHMIKANTH, T R (The Indian Journal of Animal Reproduction, 2023)
A case of unilateral ectopic testes in a one year old pugin the subcutaneous tissue is reported.